Basketball jones: Fan passion, motives, and reactions to the suspension of the National Basketball Association season due to COVID-19. (May 2021) - Schellenberg, Benjamin; Verner-Filion, Jérémie; Quach, Allen; Bailis, Daniel
Abstract: The suspension of the 2019–2020 National Basketball Association (NBA) season due to the COVID-19 pandemic meant that NBA fans were unable to engage in an activity that they loved in the midst of a global health crisis. In this research, we assessed if fan responses to the suspension were associated with different types of fan passion and motives. Shortly after the NBA season suspension, NBA fans ( N  = 395) completed online surveys assessing harmonious and obsessive passion for being an NBA fan, motives for watching games, and various attitudes and responses to the suspension. We found that both fan passion and motives predicted responses to the suspension, particularly obsessive passion which predicted greater levels of distress, coping responses, and negative attitudes toward the suspension. These findings have implications for both the passion and fan motives literatures. Highlights: Obsessive passion was associated with distress during the season suspension. Obsessive passion was associated with negative attitudes toward the suspension. Escape and social interaction fan motives predicted more perceived stress.